The role of Hippo pathway in ferroptosis - Xiang, Jiangxia; Jiang, Mengmeng; Du, Xing (Frontiers in Oncology, 2023)
Hippo pathway is mainly composed of serine/threonine kinase MST1/2, LATS1/2 and transcriptional coactivator YAP, and is closely related to cell growth, survival, proliferation, migration, size control of tissues and organs, and tumorigenesis and development. Ferroptosis is a regulated form of cell death characterized by the accumulation of iron-dependent reactive oxygen species (ROS) and the depletion of plasma membrane polyunsaturated fatty acids (PUFAs), which is caused by the imbalance of oxidation and antioxidant system. This article elaborated the role of Hippo pathway in ferroptosis, providing ideas for the regulation of cell fate and the treatment of tumors.